Crystal structure of a short‐chain dehydrogenase/reductase from Burkholderia phymatum in complex with NAD. Issue 2 (28th January 2022) - Alenazi, Jawaher; Mayclin, Stephen; Subramanian, Sandhya; Myler, Peter J.; Asojo, Oluwatoyin A.
Abstract : The crystal structure of a short‐chain dehydrogenase/reductase from Burkholderia phymatum offers insights into its possible functions and likely inhibitors of its enzymatic functions. Abstract : Burkholderia phymatum is an important symbiotic nitrogen‐fixing betaproteobacterium. B. phymatum is beneficial, unlike other Burkholderia species, which cause disease or are potential bioagents. Structural genomics studies at the SSGCID include characterization of the structures of short‐chain dehydrogenases/reductases (SDRs) from multiple Burkholderia species. The crystal structure of a short‐chain dehydrogenase from B. phymatum ( Bp SDR) was determined in space group C 2221 at a resolution of 1.80 Å. Bp SDR shares less than 38% sequence identity with any known structure. The monomer is a prototypical SDR with a well conserved cofactor‐binding domain despite its low sequence identity. The substrate‐binding cavity is unique and offers insights into possible functions and likely inhibitors of the enzymatic functions of Bp SDR.